Implementation of the Mckinsey 7s Model with Employee Job Satisfaction - Fariz Aqil Zu’am; Kristiana Haryanti (Eduvest - Journal of Universal Studies, 2026)
This study aims to explore the relationship between the McKinsey 7S model and employee job satisfaction at PT XYZ, focusing on the complex interactions of organizational elements that influence job satisfaction. In the context of globalization and digital disruption, job satisfaction has become a crucial indicator in human resource management, impacting employee performance, commitment, and leadership behavior. Although 64.9% of Indonesian employees report job satisfaction, approximately one-third of the workforce still experiences dissatisfaction. This study employs a quantitative approach with a sample of 200 employees and measurement instruments developed based on Spector's theory (2022) and Waterman Jr. et al. (1980). The analysis results indicate that the implementation of the McKinsey 7S model has a positive and significant relationship with employee job satisfaction (; ). Each component of the model—including strategy, structure, systems, and skills—shows a significant influence on job satisfaction, while aspects of shared values and leadership style do not exhibit significant relationships. These findings highlight the importance of alignment among organizational elements to enhance job satisfaction, as well as the need for a deeper approach to leadership development and shared values within the context of PT XYZ. The practical implications suggest that businesses should prioritize strengthening strategy formulation, organizational structure clarity, system efficiency, and skills development programs to enhance employee job satisfaction.